Adjacent and diagonal coupling mechanism by even-branched resonator for adjustable radiometric filtering applications. (October 2022) - Kayser Azam, S.M.; Zakir Hossain, A.K.M.; Ibrahimy, Muhammad I.; Motakabber, S.M.A.; Shazzadul Islam, Md.; Othman, Mohamadariff
Highlights: A novel coupling mechanism for intelligent radiometric systems. Resonators with adjacent and diagonal coupling, and odd/even dependency on branch number. Coupling with even number of branches and even-numbered branch-lines. 6-in-1 solution i.e., bandpass operation, harmonic suppression, quality-factor enhancement, switching ability, tunability, and digitized coupling. Abstract: Radio frequency-based measurement components utilize differently designed resonators to adjust various filtering characteristics. We introduce a unique coupling mechanism of a novel even-branched resonator that alone can adjust 6 radiometric filtering characteristics i.e., bandpass operation, harmonic suppression, quality-factor enhancement, switching ability, tunability, and digitized coupling. In our design, even-branched resonators have inter-resonator magnetic coupling while each end of their branch-lines has intra-resonator electrical coupling. Using the prominent magnetic coupling, adjacently coupled- and diagonally coupled- resonators are developed. A short-circuited stepped-impedance parallel technique is applied to achieve enhanced quality-factor and switchable/tunable bandpass filtering features. Characteristics of our radiometric resonator are determined by the odd/even dependency on its branch number. Our resonator couples with its another identical unit only when it has an even number of branches and is coupled by branch-lines that are also even-numbered. With novel digitized coupling characteristics, our resonator provides a 6-in-1 solution for intelligent radiometric systems.